Emotional empathy in pedagogy. - Namazova Umida Saydullayevna (Periodica Journal, 2023)
Today you often hear the word, but less know the feelings. This term does not mean certain actions in the perception of experience - it is a complex part of gestures, words, feelings, emotions that speak about these actions. Empathy is the ability to understand the events that happen to a person and, if necessary, sympathize with them. Such actions happen completely consciously. There are some nuances when using this term. Thus, in psychology, empathy is a natural expression of feelings in empathy
Keywords: empathy; psychology; person; expression